GAMBARAN PEMANFAATAN KMS OLEH KADER POSYANDU BALITA SEHAT DI DUSUN BEDOYO KIDUL,DESA BEDOYO, KECAMATAN PONJONG, KABUPATEN GUNUNGKIDUL, YOGYAKARTA - Intan Nugroho; Budi Rahayu (MEDIA ILMU KESEHATAN, 2016)
Background: A sensitive indicator to monitor child growth is weight changes. Monitoring children health is one of Posyandu’s (Integrated Services Post) activities. KMS is a card that is utilized to record children growth. It is very pivotal for cadres to have knowledge and skill to fill the card, especially the weight graph, so the interpretation will be accurate. In instance, malnutrition should be early detected to provide immediate intervention. Objective: This study aimed to explore the KMS utilizationby cadres at Posyandu “Balita Sehat” in Bedoyo Kidul, Bedoyo village, Ponjong Sudistrict, Gunungkidul Regency. Research method: This was a survey study, with non-analytic descriptive design. Population was 12 active cadres in Bedoyo Kidul, Bedoyo village, Ponjong Sudistrict, Gunungkidul Regency. All cadres were involved in this study. Research result: The result showed that the KMS utilization by cadres was in poor category, both for knowledge and follow-up intervention (9 respondents, 75%). Conclusion: The KMS utilization by cadres in Bedoyo Kidul, Bedoyo village, Ponjong Sudistrict, Gunungkidul Regency was in poor category. Key words: KMS utilization, Cadres